Multidimensional pain profiles in four cases of chronic non-specific axial low back pain: An examination of the limitations of contemporary classification systems - Rabey, Martin; Beales, Darren; Slater, Helen; O'Sullivan, Peter (Churchill Livingstone, 2015)
Classifying patients with chronic low back pain (CLBP) may facilitate targeted treatment, and optimise outcomes. Most classification systems (CS) do not consider multiple, interacting dimensions (for example, psychological or movement dimensions) involved in the lived experience of people with CLBP. A framework incorporating these multiple dimensions, and acknowledging individual variability, could provide a pathway to better assess and treat people with CLBP. Here we explored this proposition, presenting four cases (P1e4), profiling their clinical presentations within a multidimensional framework.P1's profile was characterised by localised lumbar sensitisation consistent with dominant peripheral nociception. P2 presented a ‘mixed’ profile characterised by localised lumbar hypersensitivity, combined with factors suggestive of centrally-mediated facilitation of nociception. P3's profile suggested widespread hypersensitivity possibly reflective of dominant centrally-mediated pain mechanisms. P4's profile was characterised by dominant psychosocial factors and comorbidities. These cases are discussed in relation to contemporary CLBP CS, highlighting the complexity of these disorders and limitations of CS for people with CLBP and their treating health professionals. This paper reinforces the need for a consensus CS for people with CLBP that is flexible, has clinical utility and considers all relevant dimensions.